Nontransformed, GM-CSF–dependent macrophage lines are a unique model to study tissue macrophage functions - Fejer, György (National Academy of Sciences, 2013)
Macrophages are diverse cell types in the first line of antimicrobial defense. Only a limited number of primary mouse models exist to study their function. Bone marrow-derived, macrophage-CSF–induced cells with a limited life span are the most common source. We report here a simple method yielding self-renewing, nontransformed, GM-CSF/signal transducer and activator of transcription 5-dependent macrophages (Max Planck Institute cells) from mouse fetal liver, which reflect the innate immune characteristics of alveolar macrophages. Max Planck Institute cells are exquisitely sensitive to selected microbial agents, including bacterial LPS, lipopeptide, Mycobacterium tuberculosis, cord factor, and adenovirus and mount highly proinflammatory but no anti-inflammatory IL-10 responses. They show a unique pattern of innate responses not yet observed in other mononuclear phagocytes. This includes differential LPS sensing and an unprecedented regulation of IL-1α production upon LPS exposure, which likely plays a key role in lung inflammation in vivo. In conclusion, Max Planck Institute cells offer an useful tool to study macrophage biology and for biomedical science.